Dual-Mode Dielectric Waveguide Monoblock Filter Design - Wu, Yahui; Jin, Lukui; Xie, Zhenxiong (Journal of Electronics and Electrical Engineering, 2022)
This paper presents a design of dielectric waveguide filter using dual-mode dielectric waveguide resonators (DWRs). The filter is formed by a ceramic monoblock, thus it is compact and ease of fabrication. The employed degenerate modes of DWR are TE101 and TE011 mode, which can be coupled by a slot on the dielectric block. The coupling between a dual-mode DWR and a single-mode DWR is realized by aperture and slot. The external coupling is realized by a silver-coated blind hole that aligns to the mode for excitation. Transmission zero (TZ) can be flexibly generated above or below passband, by changing the relative position of coupling slot. A sixth order bandpass filter working at 4.9 GHz is designed using dual- and single-mode DWRs. The filter is fabricated and measured, agreeing well with simulation. This filter has compact size, low insertion loss, good selectivity and wide spurious-free response, which is applicable to 5G base stations.